2011
DOI: 10.1159/000330017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Patients with Familial Early-Onset Alzheimer’s Disease Potentially Lacking Senile Plaques Bearing the E693Δ Mutation in Amyloid Precursor Protein

Abstract: Background/Aims: Oligomeric amyloid β (Aβ) is currently considered to induce Alzheimer’s disease (AD). We examined 2 patients with familial AD who possessed the Osaka (E693Δ) mutation in amyloid precursor protein. To the best of our knowledge, these patients are the first AD cases presumably affected with Aβ oligomers in the absence of senile plaques, and they support the Aβ oligomer hypothesis. Methods: We evaluated the clinical course, neuropsychological data, cerebrospinal fluid biomarker levels, magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…According to recent reports, 2 AD cases that were rated as PiB-negative by PiB-PET showed different primary findings -in one diffuse plaques were the primary pathological feature [3] and in the other PiB-negative Aβ accumulation was the primary finding [4]. In addition, it has been reported that PiB-PET revealed no amyloid accumulation in the cerebral cortex in cases of familial AD [5]. DLB is the second most common cause of dementia after AD in neurodegenerative disorders [6]; hence, DLB seems to be important in the differential diagnosis of PiB-negative dementia.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent reports, 2 AD cases that were rated as PiB-negative by PiB-PET showed different primary findings -in one diffuse plaques were the primary pathological feature [3] and in the other PiB-negative Aβ accumulation was the primary finding [4]. In addition, it has been reported that PiB-PET revealed no amyloid accumulation in the cerebral cortex in cases of familial AD [5]. DLB is the second most common cause of dementia after AD in neurodegenerative disorders [6]; hence, DLB seems to be important in the differential diagnosis of PiB-negative dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these studies showed good correlation with known patient pathology, whilst the study reporting increased Aβ42:Aβ40 levels cannot be validated to the patient pathology since this mutation has not been well characterized. One study also reported an increase in Aβ oligomers in the analysed neural cells and astrocytes [44], which again correlates well with the patient's phenotype [59]. Increased p-tau has been observed in patients from two different studies [43,58] and total tau has also been reported [58].…”
Section: App Mutationsmentioning
confidence: 52%
“…APPswe mutation carriers absorbed more PiB in cortex, with the cerebral glucose metabolic rate reduced, which was especially obvious in the striatum. The Aβ 42 level in CSF was increased significantly [33]. In contrast with the cerebro-absorption of 11C-PiB in sporadic AD patients, FAD with APP mutation carriers show large increases in absorption in striatum, posterior cingulate (caudate nucleus, putamen), while absorption in other cortical areas also show small increases [34].…”
Section: App Imaging Modalities: Changes Of Aβ In Brain Atrophymentioning
confidence: 86%
“…A wide range of imaging modalities, such as MRI (Magnetic Resonance Imaging), functional MRI, 11C-PiB (carbon 11-labeled Pittsburgh Compound B) PET (positron emission tomography) imaging have been utilized in supporting AD research [32,33]. In particular, some of these techniques enable the in situ detection and monitoring of senile plagues in AD patients [34].…”
Section: App Imaging Modalities: Changes Of Aβ In Brain Atrophymentioning
confidence: 99%
See 1 more Smart Citation